The textual degree of technicality as a potential factor influencing the occurrence of explicitation in scientific and technical translation - Ralph Krüger (JoSTrans: The Journal of Specialised Translation)
This paper discusses the textual degree of technicality as a potential factor influencing the frequency and distribution of explicitation in scientific and technical translation (STT). Firstly, it explains how the degree of technicality, a concept drawn from German research into languages for special purposes, is related to the subject-matter competence of the discourse participants and how these parameters – together with several others – are reflected in a corresponding ranking scale by Arntz (2001). Then, the scientific and technical corpus analysed for the purpose of this article is presented. This corpus is structured according to the textual degree of technicality and may thus be used to investigate the potential link between this parameter and the frequency and distribution of explicitation in STT. After discussing and interpreting the overall results of the analysis, the paper narrows down its perspective to compound-related explicitation as a prototypical feature of STT and proposes various examples from the corpus, attempting to relate them to the theoretical reflections made in the previous sections. The results of the corpus analysis show that a link between the textual degree of technicality and the frequency and distribution of explicitation in STT may indeed exist and that the observed correlation is quite prominent in compound-related explicitation.